2013
DOI: 10.3233/ip-130315
|View full text |Cite
|
Sign up to set email alerts
|

ICT-enabled public sector organisational transformation: Factors constituting resistance to change

Abstract: This paper suggests a revision of the commonly used model of acceptance of technical tools (TAM) for analyzing employees' attitudes towards ICT-enabled public sector organizational transformation. TAM models focus too much on technology acceptance ignoring employees' resistance to change and the reasons for innovation failure. Empirical research has shown the importance to consider these factors in organizational change projects. Basing on the example of the implementation of an electronic record system in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
2
19
2
Order By: Relevance
“…Oreg developed a change attitude scale in which five items measure the behavioral reaction level by asking about intention to resist the change initiative on a 7-point Likert-type scale. Due to the questionnaire’s length, only three items were taken for this survey: “I will look for ways to prevent the change from taking place,” “I will protest against the change,” and “I will present my objections regarding the change to management.” Although Oreg (2006) reports a Cronbach’s alpha of .77 and other surveys using this scale report a satisfactory alpha value (Chung, Su, & Su, 2012; Meier, Ben, & Schuppan, 2013), the alpha value in this study remains .61. This could be due to the length of the survey or the resistance intention items being the last scale on the questionnaire.…”
Section: Methodscontrasting
confidence: 60%
“…Oreg developed a change attitude scale in which five items measure the behavioral reaction level by asking about intention to resist the change initiative on a 7-point Likert-type scale. Due to the questionnaire’s length, only three items were taken for this survey: “I will look for ways to prevent the change from taking place,” “I will protest against the change,” and “I will present my objections regarding the change to management.” Although Oreg (2006) reports a Cronbach’s alpha of .77 and other surveys using this scale report a satisfactory alpha value (Chung, Su, & Su, 2012; Meier, Ben, & Schuppan, 2013), the alpha value in this study remains .61. This could be due to the length of the survey or the resistance intention items being the last scale on the questionnaire.…”
Section: Methodscontrasting
confidence: 60%
“…Users continue to struggle with new technology because technologies are constantly changing and there is increased pressure on employees to develop their skills so that their organizations can stay competitive. Meier, Ben and Schuppan (2013) examined employees' resistance to change and their attitude toward the adoption of electronic records system in an organization. They found that fear of losing work autonomy, social influence, and perceived quality of information significantly influenced employees' resistance to change.…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining the assertion in his 2004's work, Burnes (2015) explained this shift in the attention in connection with the lost interest in organizational development (OD) following the death of Kurt Lewin in 1947. In conclusion, despite the reduced recognition of OD which led to a declined momentum of growth in the literature of resistance to change, the Lewin's and Coch and French's seminal contribution is still serving as a foundation. McKay, Kuntz and Naswall (2013), Meier, Ben and Schuppan (2013), and Chung, Su and Su (2012) also viewed resistance to change from the side of employees reaffirming the fact that resistance to change is commonly associated with employees. This is why employees are generally assumed as the prime sources of resistance.…”
Section: Who Is Resistant To Changementioning
confidence: 97%